The Pastoral Ethos of Joseph McElroy’s Writing: Lookout Cartridge and Women and Men - Richard Anker (Transatlantica)
This article begins by proposing a very partial reading of Lookout Cartridge (1974) as a means of opening the way to a more comprehensive analysis of Women and Men (1987), an analysis which restricts itself, however, to a treatment of the main “man” of the novel, James Mayn, and in particular to his relation to his apparently suicidal mother. In doing so, it attempts to conceptualize various pastoral themes and intentions that appear in McElroy’s writing, thus finding a way of rendering an account of the author’s anti-paranoid stance with respect to science and technology, and enabling certain observations on the viability of an eco-critical approach to literature. The main objective, however, is an attempt to understand McElroy’s intention to “transmute” our technological fears without merely rejecting them, which involves a fundamental rethinking of the Art-Nature, Technè-Phusis conflict at the heart of the pastoral tradition. This rethinking, as it is deployed by the text of Women and Men, enables a critique of Western power and of its will to domination and destruction that appear infinitely capable of ignoring themselves. What McElroy’s pastoral ethos ultimately amounts to is a respect for the enigma of appearance in its difference from nature, an ethos which neither dominant modes of power nor eco-critical approaches to its catastrophic effects seem eager to acknowledge.